2020
DOI: 10.33774/coe-2020-kx2rq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Effects of the COVID-19 Pandemic on Physical Activity in U.S. Adults

Abstract: Purpose: COVID-19 restrictions, social-distancing, and quarantining may inhibit U.S. adults from attaining recommended levels of physical activity. The aims of this study were to examine the early impact of the COVID-19 pandemic on physical activity in U.S. adults during the first month of COVID-19 restrictions, and whether changes in physical activity levels differed by demographic characteristics. Method: U.S. adults completed an online survey between April 10-May 5, 2020. Participants were recruited through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 16 publications
4
18
0
5
Order By: Relevance
“…We also report a trend in decreasing weekly energy expenditure along with an increase in body weight during the peak-lockdown. With people staying indoors (in some cities and states), the closures of many local parks and recreation areas, and cancellations of gyms and organized sports activities, these findings are not surprising and supported by other studies [ 35 , 36 ]. Moreover, increasing PA can reduce cravings for high-calorie foods as well as mood [ 37 ].…”
Section: Discussionsupporting
confidence: 56%
“…We also report a trend in decreasing weekly energy expenditure along with an increase in body weight during the peak-lockdown. With people staying indoors (in some cities and states), the closures of many local parks and recreation areas, and cancellations of gyms and organized sports activities, these findings are not surprising and supported by other studies [ 35 , 36 ]. Moreover, increasing PA can reduce cravings for high-calorie foods as well as mood [ 37 ].…”
Section: Discussionsupporting
confidence: 56%
“…Early peer‐reviewed COVID‐19 research has shown MVPA decreases in China (Qin et al, 2020), the United States (Dunton et al, 2020; Meyer et al, 2020), and Europe (Cheval et al, 2020). Based on this prior research, we hypothesised that Canadians would also show an overall decrease in MVPA since the pandemic restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Only preliminary evidence is currently available following the immediate global and economic social change caused by the pandemic, with these data revealing acute declines in PA ( Dunton et al, 2020 ; Gallo et al, 2020 ; Meyer et al, 2020 ). These changes are likely in part a result of not only sudden disruption to an individual's environment and daily routine, but also a result of diminished mental health (i.e., increased anxiety, stress, depression).…”
mentioning
confidence: 99%